EFFECTIVITY OF Lepironia articulate Retz (Domin.) AS AN ABSORBEND OF HEAVY METALS FE AND MN ACID MINE DRAINAGE - Fira Hendri; Eddy Ibrahim; Hilda Zulkifli (BIOVALENTIA: Biological Research Journal, 2023)
Indonesia is one of the world's largest coal-producing countries. Most coal mining activities are conducted using the open-pit method. A classic problem caused by mining activities is acid mine drainage (AMD). Various conventional methods have been developed to increase the pH of the water and remove heavy metals such as iron (Fe) and manganese (Mn) in acid mine drainage, including chemical precipitation, coagulation, flocculation, microorganisms, adsorption, and passive treatment methods. In this study, a passive treatment method using constructed wetlands with phytoremediation techniques using L. articulate plants was employed. This study aims to analyze the effectiveness of the L. articulate plant in increasing the acidity of water and reducing the levels of Fe and Mn metals dissolved in acid mine drainage. The results of the initial sample analysis of acid mine drainage showed a pH of 2.8. The initial values of Fe met-al concentrations were 0.09 mg/L and Mn 8.10 mg/L. After the phytoremediation process, it was found that L. articulate plants were effective in increasing the pH value and reducing the concentrations of dissolved Fe and Mn metals in acid mine drainage within 20 days. The percentage reduction was 93.33% in the organic reactor and 55.56% in the inorganic reactor for Fe metal concentrations. For Mn metal reduction, the percentages were 38.02% in the organic reactor and 25.80% in the inorganic reactor.